The Baro-Adrenal Axis - Sanjay Kalra; Ashok Kumar; Nitin Kapoor (Journal of the Pakistan Medical Association, 2024)
The adrenal gland is a player in the Ominous Octet of obesity, which lists eight endocrine contributors to the development of obesity. Baro-adrenal axis describes the bidirectional, multifaceted link between weight homoeostasis and adrenal function, in health and disease. This communication lists the various ways in which adrenal function influences, and is impacted by, obesity. Keywords: Adrenal, Cushing’s syndrome, obesity, overweight, person centred care, pheochromocytoma, stress